Observation after surgery for low grade glioma: long-term outcome in the light of the 2016 WHO classification - Jansen, Elena; Hamisch, Christina; Ruess, Daniel; Heiland, Dieter Henrik; Goldbrunner, Roland; Ruge, Maximilian I.; Schnell, Oliver; Grau, Stefan J. (Journal of Neuro-Oncology, 2019)
Purpose: To provide detailed long-term data after initial observation for patients after histological confirmation of low grade (WHO II) gliomas according to molecular stratification. Methods: A series of 110 patients with watchful waiting strategy after initial surgery for LGG and re-surgery at tumor progression were analyzed. Progression-free survival, time to malignant transformation, post-recurrence survival, and overall survival were estimated with the Kaplan–Meier method. Prognostic factors were identified by the Log Rank test and Cox multivariate proportional hazards model. Results: The cohort comprised 18 IDH wild type (IDHwt) and 53 IDH mutated (IDHmut) astrocytomas, and 39 IDH mutated and 1p 19q co-deleted (IDHmut/codel) patients. The median follow-up was 126 (95% CI 109–143) months. Surgery was gross total resection in 58, subtotal resection in 28, and biopsy in 24 patients. Progression-free survival rates at 5, 10 and 15 years was 38% 18% and 1%. The corresponding malignant transformation rates were 17%, 39% and 71%. The initial extent of resection influenced progression-free survival, time to malignant transformation and overall survival. Molecular subtype IDHmut/codel was the strongest prognostic factor for overall survival and for time to malignant transformation. Conclusion: The strongest determinant of the patients’ course after initial watchful waiting was the molecular tumor status. Extensive resection may increase time to progression and malignant transformation. Observation may be justified in selected patients.
CRIS-Team Scopus Importer:2023-09-13
Keywords: 1p19q co-deletion; IDH mutation; Low grade glioma; Observation